PENGARUH METODE SAVI TERHADAP RESPON DAN HASIL BELAJAR SISWA KELAS X SMA NEGERI 2 SUNGAI RAYA - Anamas, Fauzan Zasqi; Hairida, Hairida; Sahputra, Rachmat (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractResponse and learning output of X grade students at SMAN 2 Sungai Raya were unsatisfactory. This research was conducted to determine whether there was a significant difference between student responses taught using SAVI method and conventional learning method, and whether there was a significant difference between learning output of students taught SAVI method and conventional learning method, and to determine effect size of SAVI method toward student response and learning output on hydrocarbon. This research used quasi experimental with Nonequivalent Pretest Postest Control Group Design. The research sample consisted of XA class as the experimental group and XB class as the control group selected by random sampling technique. Pretest, posttest, and response questionnaire were used to collect data. Based on response questionnaire and posttest data analysis using the U-Mann Whitney test (α = 5%), Asymp.Sig (2-tailed) were 0.000 and 0.039 respectively. This indicated that there were a significant difference between response and learning output of students taught using SAVI method and conventional learning method. SAVI method gave 80.78% effect toward student response and 25.18% toward student learning output. Keywords: Hydrocarbon, Learning Output, SAVI Method, Student Response